2008
DOI: 10.1007/s11259-008-9062-x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for resistance to footrot – the use of hoof lesion scoring to quantify footrot in sheep

Abstract: So that genetic studies can be undertaken on footrot in sheep, it is necessary that a reliable and repeatable method to categorise the phenotype is available. This paper summarises the methods used and results obtained from 1600 hoof lesion scores of 100 mixed-age ewes independently scored twice by two trained operators. Using a 5-pont scale describing the severity of foot lesions, residual correlations were used to assess agreement between scorers and scoring occasions. Data were analysed using both zero-1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 7 publications
0
34
0
3
Order By: Relevance
“…Just as the profitability of meat, milk and fleece production drops due to foot diseases, serious economic losses are also experienced due to premature births and culling animals from the herds [11,[29][30][31][32] . It was observed that the general health of the animals visited, especially in the pen/stall season, was weak, and that the wool had fallen out from many different regions of their bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as the profitability of meat, milk and fleece production drops due to foot diseases, serious economic losses are also experienced due to premature births and culling animals from the herds [11,[29][30][31][32] . It was observed that the general health of the animals visited, especially in the pen/stall season, was weak, and that the wool had fallen out from many different regions of their bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep foot diseases, which directly impact profitability due to the negative impact on animal welfare, pose a significant threat [6][7][8][9][10][11] . Because sheep have such a high tolerance of pain, as long as they do not have extreme foot lesions, they will not limp [9,12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the management group effect is confounded with the score date (with a group only scored on 1 or 2 successive days), so that the scorer by group effect may partly be a time effect. The repeatability of scorers has been investigated in a separate analysis (Conington et al, 2008) showing high consistency between scorers and between subsequent scores by the same scorer on the same day.…”
Section: Discussionmentioning
confidence: 99%
“…The scoring system described by Egerton and Roberts (1971) was implemented as described in detail by Conington et al (2008) and summarised in Table 1. Animals were inspected and awarded a score of 0 (healthy) to 4 (severe footrot) for each hoof, where a score of 1 may indicate scald or early stage footrot.…”
Section: Scoringmentioning
confidence: 99%
“…Quanto à distribuição das lesões nos animais estudados, foi observado que os membros anteriores foram mais acometidos (57%) que os membros posteriores (23%) similar à observação de outros autores (Pugh 2004, Wenger 2007. Porém, existem estudos que descrevem uma maior incidência de lesões nos membros posteriores (Conington et al 2008). A presença de lesões nos membros anteriores faz com que os animais pastem ajoelhados, alteração comumente observada nas ovelhas utilizadas.…”
Section: Discussionunclassified